GAYA DAN METODE PENAFSIRAN AL-QUR’AN - Patsun (CENDEKIA: Jurnal Studi Keislaman, 2021)
Al-Qur'an is a holy book revealed by Allah SWT. to the Prophet Muhammad as a human guide, a way of life for the people of the whole world. In order for the Qur'an to truly be a guide for mankind, understanding the verses of the Qur'an is very important, through its interpretations, as well as interpretations that can reflect the development and style of thought of the interpreter. The history of the interpretation of the Qur'an is Islam itself. This means that the history of the interpretation of the Qur'an is as old as the history of the journey of Islam as a religion, so that the two become identical and inseparable. Interpretive activity, of course, started when the Prophet Muhammad delivered the message of God which came in the form of the Qur'an.